2016
DOI: 10.1039/c6cp06643g
|View full text |Cite
|
Sign up to set email alerts
|

Chain conformation-dependent thermal conductivity of amorphous polymer blends: the impact of inter- and intra-chain interactions

Abstract: Polymers with high thermal conductivities are of great interest for both scientific research and industrial applications. In this study, model amorphous polymer blends are studied using molecular dynamics simulations. We have examined the effects of inter- and intra-chain interactions on the molecular-level conformations of the blends, which in turn impact their thermal conductivity. It is found that the thermal conductivity of polymer blends is strongly related to the molecular conformation, especially the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 40 publications
4
96
0
Order By: Relevance
“…This high thermal conductivity is attributed to the H-bond networks formed by these three polymer blends (PVA, lignin and gelatin) to supply more heat transfer pathways, as illustrated in Fig In addition to bridging different polymer chains to form heat-transfer networks (bridging effect), H-bonds could also serve as "soft grips" to suppress the segmental rotation of polymers, which reduces phonon scattering and thus leading to a higher thermal conductivity [53,54]. Through MD simulations of amorphous polymer blends, Wei et al [55] proposed that locally ordered lamellar structures could form in the polymer blends due to the large inter-chain interactions and thus enhancing the thermal conductivity.…”
Section: Fig 13 Thermal Conductivity Of Polymer Blends By Engineerinmentioning
confidence: 99%
“…This high thermal conductivity is attributed to the H-bond networks formed by these three polymer blends (PVA, lignin and gelatin) to supply more heat transfer pathways, as illustrated in Fig In addition to bridging different polymer chains to form heat-transfer networks (bridging effect), H-bonds could also serve as "soft grips" to suppress the segmental rotation of polymers, which reduces phonon scattering and thus leading to a higher thermal conductivity [53,54]. Through MD simulations of amorphous polymer blends, Wei et al [55] proposed that locally ordered lamellar structures could form in the polymer blends due to the large inter-chain interactions and thus enhancing the thermal conductivity.…”
Section: Fig 13 Thermal Conductivity Of Polymer Blends By Engineerinmentioning
confidence: 99%
“…This is because thermal transport in amorphous polymer is dominated by the covalent bonds along the chain backbones and when such backbones are extended, thermal conductivity increases. 14,15 In bulk condensed polyelectrolytes, where the counterion concentration is high and the interchain interaction is strong, the counterion condensation theory suggests that the polymer chain will collapse. [16][17][18] Thus, the observed thermal conductivity increase (in Fig.…”
Section: The Molecular Conformation Has No Effect On Thermal Conductimentioning
confidence: 99%
“…4,5 In polymers, along the molecular backbone direction heat transfer can be very efficient due to the strong covalent bonds, while in the interchain direction heat transfer is much less efficient due to the weak non-bonding interactions. [6][7][8][9] A number of recent studies have revealed that polymer thermal conductivity is strongly related to its molecular level conformation. 6,8,[10][11][12][13][14] For example, stiffer molecular backbones can make the chains straighter even in the amorphous state 15 and thus increase the amount of heat that can be transferred through the strong backbone.…”
Section: Introductionmentioning
confidence: 99%